Pasar Bebas dan Pembangunan Ekonomi Daerah Menurut Syari'at Islam - Munir, Misbahul (Jurnal Aplikasi Manajemen, 2009)
Free market competition is being reality nowadays. But in the Islam id teaching free market competition in also regulated morally. Competition in Islamic rule means to do better and more useful than order. There is an reason to attack or deceive the other competitors. Everything done by the Islamic confessors must be devotional, so must be their behavior in the market competition in arranging the local economy we must always remember that however there is no border for the growth of supply and demand nowadays. So really there no is total autonomy, because the local markets also need other local supplies and demands.